1987
DOI: 10.1038/bjc.1987.246
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of erythroleukaemic cells by photoactivation of endogenous porphyrins

Abstract: Cancer therapy ideally should be based on high selectivity of the therapeutic agent for the transformed cells, low specificity for normal tissues and high cytotoxic efficiency to the target tumour. These requirements are partially fulfilled by haematoporphyrin derivative (HPD) phototherapy.The method is based on the capability of porphyrins to be selectively localized in malignant tumours. Light activation of the localized porphyrin induces damage to mitochondria, cellular organelles, membranes, DNA, and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
114
0
6

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(121 citation statements)
references
References 18 publications
1
114
0
6
Order By: Relevance
“…Other approaches for achieving better localisation include local administration of the photosensitiser (Amano et al, 1988;Bachor et al, 1992). Recently, there has been considerable interest in a different approach to PDT in which a precursor, ALA, is administered and synthesis of the photosensitiser, PpIX, accomplished in situ (Pottier et al, 1986;Malik & Lugaci, 1987;Malik et al, 1989;Divaris et al, 1990;Kennedy et al, 1990;Bedwell et al, 1992;Kennedy & Pottier, 1992;Loh et al, 1992Loh et al, , 1993aRebeiz et al, 1992). The synthesis of ALA is the rate-limiting step in non-erythroid cells in the pathway of haem biosynthesis (Martin, 1985) (Rebeiz et al, 1992).…”
mentioning
confidence: 99%
“…Other approaches for achieving better localisation include local administration of the photosensitiser (Amano et al, 1988;Bachor et al, 1992). Recently, there has been considerable interest in a different approach to PDT in which a precursor, ALA, is administered and synthesis of the photosensitiser, PpIX, accomplished in situ (Pottier et al, 1986;Malik & Lugaci, 1987;Malik et al, 1989;Divaris et al, 1990;Kennedy et al, 1990;Bedwell et al, 1992;Kennedy & Pottier, 1992;Loh et al, 1992Loh et al, , 1993aRebeiz et al, 1992). The synthesis of ALA is the rate-limiting step in non-erythroid cells in the pathway of haem biosynthesis (Martin, 1985) (Rebeiz et al, 1992).…”
mentioning
confidence: 99%
“…Tissue concentrations were computed from the fluorescence values obtained by a titration of a protoporphyrin IX (PPIX) standard (Porphyrin Products, Logan, UT, USA). Protoporphyrin IX was used as the standard as previous reports demonstrated that PPIX is the major contributor to the fluorescence detected after exposure of cells to 8-ALA (Malik and Lugaci, 1987;Kennedy and Pottier, 1992;Hua et al, 1995). Values obtained in the present study were almost identical to those we reported previously when porphyrin fluorescence was measured on tissue extracts (Hua et al, 1995).…”
Section: Detection Of Porphyrin Fluorescence In Tissue Homogenatesmentioning
confidence: 99%
“…The increased selective effects on TT treated at 60 min p.i. could also be the result of translocation within the cell of porphyrin from the mitochondrion to less sensitive sites (Kessel, 1986;Malik & Lugaci, 1987). Since PpIX is formed in the mitochondrion and because the mitochondrion is very sensitive for PDT damage (Hilf, 1986;Salet, 1986) an increased effect may be expected when treating at an interval where the rate of fluorescence increase is maximal as done in group C.…”
Section: Fluorescence Kinetic Studiesmentioning
confidence: 99%